Academic integrity and plagiarism: A review of the influences and risk situations for health students - Jiang, H.; Emmerton, Lynne; McKauge, L. (Routledge, 2013)
Health professions are increasingly focusing on the development of integrity and professionalism in students of Health disciplines. While it is expected that Health students will develop, and commit to, the highest standards of conduct as undergraduates, and henceforth through their careers, the pressures of assessment and external commitments may lead to both unintentional and intentional plagiaristic behaviours. Exponential growth in Internet resources and new information technologies, as well as individual belief systems or naivety about the authorship attribution convention, suggest complexity in understanding the risks and factors associated with academic plagiarism. This paper reviews the education literature to provide an insight for academics into reasons for student plagiarism and, where possible, management of these risks. Our review refers to the health professions as a discipline in which academic conduct in students should be at the highest possible standard.